Pengaruh Motivasi Internal Dan External Terhadap Niat Berkunjung Kembali Dimediasi Oleh Kepuasan - Kusdaryana, Made Donny; Koerniawaty, Francisca Titing; Darsana, Made (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
This research aims to analyze the influence of internal motivation and external motivation on intention to revisit which is mediated by satisfaction with visiting Pualu Nusa Penida. This research uses a quantitative descriptive approach. Data was collected through observation, interviews and distributing questionnaires to tourists. The research sample was 100 tourists, while the sampling technique used purposive sampling. Data was collected from 100 respondents using a questionnaire and analyzed using SEM PLS. Evaluation of the PLS-based structural model, apart from looking at the R-square and Q-square values, can also be carried out by fulfilling several criteria such as the Chi-Square Test, GFI (Goodness of Fit Index), SRMR (Standardized Root Residual) and NFI (Normal Fit Index) . Based on the results of the analysis using statistical tests, the results of this research are, internal motivation has a significant positive effect on tourist satisfaction, external motivation has a significant positive effect on tourist satisfaction, tourist satisfaction also has a positive effect on tourists' intention to revisit, internal motivation has a significant positive effect on intention. Tourists' return visit and external motivation have a positive influence on tourists' intention to return.